2022
DOI: 10.3389/fsoc.2022.1007107
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on the provision of instrumental help by older people across Europe

Abstract: The outbreak of the COVID-19 pandemic in early 2020 introduced new challenges to social cohesion across Europe. Epidemiological control measures instituted in almost all European countries have impacted the possibility to provide help to others. In addition, individual characteristics contributed to whether individuals were able and willing to provide help to or receive help from others. Against this background, we focus on how private support networks of individuals aged 50 years and older across Europe were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Our findings revealed that the overall situation of care receivers improved in the sense that home care from outside the household was again more widely available in summer 2021 compared to one year before in nearly all European regions. There are two interpretations for this pattern: First, due to the vaccination campaign, which started at the end of 2020 and picked up speed in spring 2021 in most European countries, epidemiological control measures and restrictions that had been introduced could be relaxed so that social contacts as well as support in general (and care in particular) were possible again more easily [ 23 ]. This was particularly true in Western and Southern European countries, which had been hit hardest by the first wave of the pandemic in 2020 and hence had more restrictive control measures in place [ 52 ] compared to one year later when vaccination was available for large parts of the population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings revealed that the overall situation of care receivers improved in the sense that home care from outside the household was again more widely available in summer 2021 compared to one year before in nearly all European regions. There are two interpretations for this pattern: First, due to the vaccination campaign, which started at the end of 2020 and picked up speed in spring 2021 in most European countries, epidemiological control measures and restrictions that had been introduced could be relaxed so that social contacts as well as support in general (and care in particular) were possible again more easily [ 23 ]. This was particularly true in Western and Southern European countries, which had been hit hardest by the first wave of the pandemic in 2020 and hence had more restrictive control measures in place [ 52 ] compared to one year later when vaccination was available for large parts of the population.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, day-care facilities where care receivers can spend some of their time often had to close [11] and health services and treatments experienced disruptions due to installed epidemiological control measures [17][18][19][20][21]. There is also evidence that help and support by closer family and friends increased during this phase [12,[22][23][24][25] as those had to compensate for the reduced supply of formal care providers. As health care services were often unavailable, care receivers forwent medical treatments [4,[26][27][28][29] and they also showed indications of physical and mental health problems [22,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings revealed that the overall situation of care receivers improved in the sense that home care from outside the household was again more widely available in summer 2021 compared to one year before in nearly all European regions. There are two interpretations for this pattern: First, due to the vaccination campaign, which started at the end of 2020 and picked up speed in spring 2021 in most European countries, epidemiological control measures and restrictions that had been introduced could be relaxed so that social contacts as well as support in general (and care in particular) were possible again more easily [23]. This was particularly true in Western and Southern European countries, which had been hit hardest by the first wave of the pandemic in 2020 and hence had more restrictive control measures in place [49] compared to one year later when vaccination was available for large parts of the population.…”
Section: Discussionmentioning
confidence: 99%